2019
DOI: 10.1108/arj-02-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Corporate voluntary carbon disclosure strategy and carbon performance in the USA

Abstract: Purpose This study aims to examine whether good carbon performers disclose more carbon information overall than poor performers, and if yes, how firms select different types of carbon information to signal their genuine superior carbon performance. Design/methodology/approach The level of disclosure is measured based on content analysis of Carbon Disclosure Project (CDP) reports. The study sample consists of 487 US companies that voluntarily participated in the CDP survey from 2011 to 2012. The authors use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Unfortunately, the empirical results for this research question are not conclusive. Luo and Tang (2014b) and Datt et al (2019b) find support for signalling theory by showing that the extensiveness of carbon disclosure is positively associated with the firm's carbon mitigation performance. Ott et al (2017) present similar but relatively weak evidence.…”
Section: The Relationship Between Carbon Performance and Carbon Discl...mentioning
confidence: 88%
“…Unfortunately, the empirical results for this research question are not conclusive. Luo and Tang (2014b) and Datt et al (2019b) find support for signalling theory by showing that the extensiveness of carbon disclosure is positively associated with the firm's carbon mitigation performance. Ott et al (2017) present similar but relatively weak evidence.…”
Section: The Relationship Between Carbon Performance and Carbon Discl...mentioning
confidence: 88%
“…explained earlier, previous research has employed different indicators as proxies of environmental performance. Carbon emission data from the CDP database(Datt et al (2020);Giannarakis et al (2017);Luo and Tang (2014), hazardous waste produced(Iatridis (2013), toxic waste recycled(Al-Tuwaijri et al (2004), and waste diversion rate(Oates and Moradi-Motlagh (2016). Our study focuses on mandatorily disclosed to government annual carbon emissions volume data under the NGER Act, argued to be superior since it relates to the same fiscal year for each company, is determined using the same stipulated definitions and method, and is reliable since it is subject to random audit by regulators.Environmental performance is measured as 1-year lagged change in carbon emissions from one year to the next (Scope 1 plus Scope 2) deflated by sales from the previous period.…”
mentioning
confidence: 99%
“…Carbon emission is becoming increasingly important for stakeholders who are interested in the effects of global warming. Stakeholders demand transparent information and firms tend to disclose their real obligations to fulfill their commitment and to improve their environment-based decision making (Datt et al, 2018) [9]. Additionally, to cope with the rising attention on the environment, firms may have the intent of persuading stakeholders that they are concerned about the environment and voluntary disclosure is a way to spread the message.…”
Section: Voluntary Disclosure Of Carbon Emissionmentioning
confidence: 99%
“…Firms that voluntarily disclose information about carbon emissions, which can be negative information, will signal that they are performing their required social responsibilities in good faith. Datt et al (2019) [9] found that firms use carbon performance as a signal when they are better than other firms. In other words, firms with a high performance in their use of voluntary CDP are more engaged in reporting their commitment to controlling carbon emissions.…”
Section: Voluntary Disclosure Of Carbon Emissionmentioning
confidence: 99%